Assessing holistic developmental gaps among the students during the COVID-19 Pandemic: An analysis of physical, socio-emotional, and personal developmental aspects - Dr Anand Kumar Arya; Dr. Neeta Rani (IJRDO- Journal of Educational Research, 2025)
The Indian vision of education has always emphasized the importance of holistic development, focusing on the integrated development of body, mind, intellect, and soul. The above approach emphasizes that education is about developing kind, knowledgeable and, and well-rounded people rather than merely assisting students to achieve intellectually. Addressing students’ physical, emotional, ethical, moral, cultural, social, and intellectual requirements is crucial for advancing the nation into the twenty-first century, according to the National Education Policy 2020 (NEP 2020). The COVID-19 pandemic has challenged the education sector with hitherto unprecedented difficulties, disrupting established learning models and emphasizing the necessity for creative and flexible teaching methods (Khari, S. et al., 2024). Students had to deal with emotional and social issues in addition to intellectual ones as they made the transition to online study (Li, Y., 2023). The pandemic has underscored the importance of holistic development, as students’ overall well-being and resilience have been tested.